2022
DOI: 10.3390/ijms23042373
|View full text |Cite
|
Sign up to set email alerts
|

A Zebrafish Model for a Rare Genetic Disease Reveals a Conserved Role for FBXL3 in the Circadian Clock System

Abstract: The circadian clock, which drives a wide range of bodily rhythms in synchrony with the day–night cycle, is based on a molecular oscillator that ticks with a period of approximately 24 h. Timed proteasomal degradation of clock components is central to the fine-tuning of the oscillator’s period. FBXL3 is a protein that functions as a substrate-recognition factor in the E3 ubiquitin ligase complex, and was originally shown in mice to mediate degradation of CRY proteins and thus contribute to the mammalian circadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Regular veterinary inspections (every three months) confirmed that there were no known pathogens affecting the fish in our facility. The fbxl3 –/– line 14 is registered in the Zebrafish Model Organism Database (ZFIN) as fbxl3a tlv 0 . Eggs were derived from in-crosses of 6–9-month-old fish.…”
Section: Material Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regular veterinary inspections (every three months) confirmed that there were no known pathogens affecting the fish in our facility. The fbxl3 –/– line 14 is registered in the Zebrafish Model Organism Database (ZFIN) as fbxl3a tlv 0 . Eggs were derived from in-crosses of 6–9-month-old fish.…”
Section: Material Methods and Resultsmentioning
confidence: 99%
“…The genotyping of the 24 hpf embryos was performed via PCR followed by NlaIII restriction enzyme digestion (New England Biolabs) as previously described, 14 with some modifications.…”
Section: Material Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This fascinating model can be utilized in mutagenesis analyses and drug screening tests. It has been used to conduct experiments related to different research fields such as embryology, genetics, cancer, cardiovascular, and organ and tissue regeneration [ 43 , 44 , 45 , 46 ]. In the present report, firstly, in order to identify different cell populations in adult zebrafish testis and ovary, hematoxylin-eosin staining on paraffin sections has been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…In an illustration of the simplicity and power of the zebrafish as a genetic tool, two studies have made use of the relatively new CRISPR/Cas9 technology of gene editing to produce loss-of-function alleles of genes of interest prior to analyzing the induced phenotypes. Starting from a consanguineous family of whom several members presented macrocephaly, facial hypoplasia, hypotonia, and intellectual disability, Confino et al [5] identified the causative mutation in the FBXL3 gene encoding F-box and leucine-rich repeat protein 3 and then generated a loss-of-function allele of fbxl3a, one of the two zebrafish paralogs of this gene. Interestingly, the results suggested that in contrast to the human gene, fbxl3a is not essential for brain development, but is a key component of the circadian clock, as is the case in mice.…”
mentioning
confidence: 99%